PENDAMPINGAN PENGEMBANGAN MARKETING UMKM MIKRO TERHADAP PENINGKATA MINAT PEMBELI - Isma Wati; Kurnia Arumdani; Agung Winarno; Agus Hermawan (Jurnal Pemantik, 2022)
The purpose of assisting Kopikos MSMEs is to expand their market reach through e-commerce, namely using online platforms, social media, and marketplaces, to provide convenience for online transactions, provide changes in the perspective of Kopikos MSMEs, by providing education on the use of online media. With this observation, the aim is to assist Kopikos MSMEs so that they can maintain their business during the Covid 19 pandemic by providing business support. This study uses a qualitative descriptive method to find out a detailed description of the problems and phenomena that exist in the MSME field through interviews and observation methods. So that the result of the MSME assistance activities at Kopikos is that digital e-commerce marketing has been made by providing direct training such as logo design, Instagram, gofood, making menu lists, and taking product photos. It is hoped that Kopikos MSMEs will reach a wider market share and be able to increase sales, as well as participate in editing content on social media.